ПОГЛЯД ЗАРУБІЖНИХ ТА ВІТЧИЗНЯНИХ НАУКОВЦІВ НА ПРОБЛЕМУ МЕТАКОГНІТИВНИХ ЗДІБНОСТЕЙ - Захарчук Тетяна Миколаївна (World Science, 2019)
The article deals with theoretical concepts and approaches to the problem of meta cognitive abilities, psychological aspects of the formation and development of meta processes in adulthood and childhood. The views of scientists on the problems of the purpose of processes in psychological science are revealed. The peculiarities of the development of mental operations within the framework of metacognitivism are considered, based on the views of foreign and domestic scholars.